Exploring the perceptions of lecturers and final year students about the infusion of inclusion in initial teacher education programmes in South Africa - Nel, Mirna; Hay, Johnnie; Bekker, Tanya; Beyers, Christa; Pylman, Nicky; Alexander, Gregg; Matoti, Sheila (Frontiers in Education, 2023)
South Africa embraced the move to inclusive education after the political transformation in 1994 by partaking in and subscribing to the international Education for All (EFA) drive initiated in 1990 at the Jomtien World Conference on Education for All, which declared that all children, youth and adults should receive a basic education. Furthermore, the Salamanca Statement of 1994 the United Nations Convention on the Rights of Persons with Disabilities (CRPD) of 2006 and the Sustainable Development Goal 4 are internationally regarded as the most important influence on the transformation of education systems to become more inclusive and consequently continue to have an important influence on education policies and practices in South Africa. The key policy driving inclusive education in South Africa is Education White Paper 6 (EWP6). EWP6 affirms that teachers play a central role in implementing an inclusive education system. Therefore, training is emphasized as a key strategy to enable educators to become more inclusive in their teaching practices. The focus of this article is on Initial Teacher Education (ITE) for inclusion. Influenced by international developments to transform ITE programmes and the national endorsement of inclusive education the Department of Higher Education and Training (DHET) embarked on a project called the Teaching and Learning Capacity Development Improvement Project (TLCDIP). This project focused specifically on teacher education for inclusion in the Foundation and Intermediate Phases. The primary research aim was: To explore the perceptions of lecturers and students in ITE programmes regarding the preparation of pre-service teachers for teaching in inclusive and diverse learning environments. A qualitative research approach was employed to gain in-depth and rich data. Purposive sampling was used including students and lecturers. Open questionnaires and group interviews were employed as data collection strategies. An inductive thematic analysis showed that the following themes were identified by the participants as critical to be considered in the development and implementation of ITE programmes: Understanding inclusive education, which is also linked to knowledge; the disconnect between theory and practice, the lack of knowledge and practical experience regarding inclusive teaching strategies and how inclusion is addressed in the B Ed curriculum.